The Effect of Work Environment and Job Training on Employee Performance with Work Loyalty as an Intervening Variable at the Satpol PP Service of Sijunjung District - Yance Gafar; John Veri (Sean Institute, 2025)
This study aims to examine the extent of influence of the work environment and job training on employee performance with job loyalty as an intervening variable at the Satpol PP office of Sijunjung Regency. The data collection method was through surveys and distributing questionnaires, with a sample of 47 respondents. The analysis method used was structural equation modeling using smartpls. The results of the study showed a significant influence of the work environment on job loyalty. There was a significant influence of job training on job loyalty. There was a significant influence of the work environment on employee performance. There was an insignificant influence of job training on employee performance. There was a significant influence of job loyalty on employee performance. Work loyalty mediated the influence of the work environment on employee performance. Work loyalty did not mediate the influence of the work environment on employee performance.